The Importance of Blockholder Heterogeneity: Security Market Effects and Follow-On Activities - Hsieh, Jim; King, Tao-Hsien Dolly (Journal of Financial and Quantitative Analysis, 2019)
Recent research on blockholders focuses on activist hedge funds and documents positive stock but negative bond returns. This study investigates the role of blockholder heterogeneity on security market effects and target firm follow-on activities across three important dimensions: identity, motive, and purchasing method. We show that target firms’ security returns and post-acquisition activities strongly correlate with blockholder heterogeneity. Further, bond returns are significantly positive for firms with blockholders’ debt-assistance motive while both stock and bond returns are significantly negative in private placements. Overall, our findings highlight the importance of blockholder heterogeneity on the valuation and performance consequences in block acquisitions.